The Influence of Workload, Job Satisfaction, and Work Environment on the Work Productivity of Nurses at PKU Muhammadiyah Aghisna Kroya Hospital - Putri, Mustikaningrum Dewanti; Purnadi, Purnadi; Astuti, Herni Justiana; Endratno, Hermin (Asian Journal of Management Analytics, 2025)
This study aims to analyze the influence of workload, job satisfaction, and work environment on nurses' work productivity at PKU Muhammadiyah Aghisna Kroya General Hospital. This study used a quantitative approach with a survey method by distributing questionnaires to the entire nurse population of 120 respondents. Data analysis techniques included validity and reliability tests, classical assumptions, multiple linear regression, and F and t tests. The results of the analysis showed that workload had a positive and significant effect on nurses' work productivity, while job satisfaction and work environment did not show a significant effect. This indicates that a well-managed workload can increase productivity, but perceived satisfaction and work environment are not enough to directly drive performance. These findings strengthen the perspective of Social System Theory (SST) that nurses' work productivity is influenced by complex interactions between individuals and their environment. This study provides important implications for hospital management in designing strategies to increase productivity through effective workload management.